Oncostatin M is a FIP1L1/PDGFRA‐dependent mediator of cytokine production in chronic eosinophilic leukemia. Issue 6 (27th April 2013) - Hoermann, G.; Cerny‐Reiterer, S.; Sadovnik, I.; Müllauer, L.; Bilban, M.; Gröger, M.; Horny, H.‐P.; Reiter, A.; Schmitt‐Graeff, A.; Mannhalter, C.; Valent, P.; Mayerhofer, M.
Abstract Background Chronic eosinophilic leukemia (CEL) is a myeloproliferative neoplasm characterized by expansion of neoplastic eosinophils, tissue infiltration, and organ damage. In a subset of these patients, the FIP1L1/PDGFRA (F/P) oncoprotein is detectable. F/P exhibits constitutive tyrosine kinase activity and activates a number of signaling pathways. So far, however, little is known about the role of F/P‐dependent proteins in the pathogenesis of CEL. Methods A screen for F/P‐dependent cytokines was performed in growth factor‐dependent human cell lines lentivirally transduced with F/P. Signal transduction pathways were characterized in Ba/F3 cells with doxycycline‐inducible expression of F/P and in EOL‐1 cells. Cytokine expression was confirmed in patients' material by immunohistochemistry, immunofluorescence, and confocal microscopy. Gene expression analysis, proliferation assays, and chemotaxis assays were used to elucidate paracrine interactions between neoplastic eosinophils and stromal cells. Results We show that F/P upregulates expression of oncostatin M (OSM) in various cell line models in a STAT5‐dependent manner. Correspondingly, neoplastic eosinophils in the bone marrow were found to overexpress OSM. OSM derived from F/P + cells stimulated proliferation of stromal cells. Moreover, OSM‐containing supernatants from F/P + cells were found to upregulate production of stromal cell‐derived factor‐1 (SDF‐1)/CXCL12 in human fibroblasts. SDF‐1, in turn, induced migration of EOL‐1 cells in a dose‐dependent manner. Conclusions We have identified a F/P‐driven paracrine interaction between neoplastic eosinophils and stromal cells that may contribute to tissue fibrosis and accumulation of neoplastic eosinophils in CEL.